2008
DOI: 10.1016/j.tetlet.2008.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a library of glycosylated flavonols

Abstract: a b s t r a c tFlavonols are an important class of natural products isolated from plants. Some glycosylated flavonols showed very interesting biological activities. A library of flavonols has been made through Algar-Flynn-Oyamada reaction from 2 0 -hydroxyacetophenones and benzaldehydes. Glycosylation of these flavonols with various glycosyl donors affords a library of glycosylated flavonols. These compounds are potentially useful pharmacologically active compounds and will be studied for biological activities. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In the synthesis of α-naphthoflavone derivatives (4a-4o, Scheme 1), compound 1 served as the starting point which was easily prepared from 1,5-dihydroxynaphthalene according to our reported procedure 23 The most commonly used method for the synthesis of flavonols was the Algar-Flynn-Oyamada (AFO) reaction that employed corresponding chalcones as the starting material [24][25][26][27] . However, in the synthesis of 6,7,10-trimethoxy-α-naphthoflavonols (8a-8g), this oxidative cyclization strategy using 2'-hydroxyl benzochalcones (9a-9g, Figure 3) failed to give any desired naphthoflavonols.…”
Section: Resultsmentioning
confidence: 99%
“…In the synthesis of α-naphthoflavone derivatives (4a-4o, Scheme 1), compound 1 served as the starting point which was easily prepared from 1,5-dihydroxynaphthalene according to our reported procedure 23 The most commonly used method for the synthesis of flavonols was the Algar-Flynn-Oyamada (AFO) reaction that employed corresponding chalcones as the starting material [24][25][26][27] . However, in the synthesis of 6,7,10-trimethoxy-α-naphthoflavonols (8a-8g), this oxidative cyclization strategy using 2'-hydroxyl benzochalcones (9a-9g, Figure 3) failed to give any desired naphthoflavonols.…”
Section: Resultsmentioning
confidence: 99%
“…From a survey of the literature, we found that flavonol derivatives can be achieved by the epoxidation of corresponding flavone compounds or by the Baker–Venkataraman type of sequential cyclization‐dehydration reaction . Another Algar–Flynn–Oyamada reaction has also been widely used to make flavonols . We chose this reaction for the transformation of 3‐methylfuranochalcones 11 to angular 3‐methylfuranoflavonols 12 in the presence of NaOH (2 equiv) and H 2 O 2 (2.2 equiv).…”
Section: Resultsmentioning
confidence: 99%
“…The Claisen-Schmidt condensation of substituted benzaldehyde (3) and acetophenone derivative (1) (Goel and Dixit, 2004) in presence of aqueous potassium hydroxide produced corresponding chalcone (4) . Resulted chalcone was converted to benzylated furanoflavonoid (5) using Algar-Flynn-Oyamada reaction (Zhitao et al, 2008) by treatment with alkaline hydrogen peroxide. Further, it was debenzylated using TiCl 4 (Selvam et al, 2009) in dry DCM under N 2 atmosphere affording 3,3 0 ,4 0 -trihydroxy-4H-furo[2,3-h]chromen-4-one (6) (Scheme 1; Fig.…”
Section: Chemistrymentioning
confidence: 99%
“…R 1 = R 2 = R 4 = H, R 3 = OCH 2 Ph (f). R 1 = R 4 = H, R 2 = OMe, R 3 = OCH 2 Ph (g on type 2 diabetes mellitus has advocated that a-glucosidase inhibitors are most effective in reducing PPHG in typical Asian dietary conditions (Zhitao et al, 2008). Its use is also associated with a slight decrease in fasting glucose concentrations.…”
Section: Chemistrymentioning
confidence: 99%